1997
DOI: 10.1038/bjc.1997.472
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical study of altered immunomodulatory molecule expression in head and neck squamous cell carcinoma

Abstract: Summary For the presentation of peptide antigens to cytotoxic CD8+ T lymphocytes of the immune system, the expression of human leukocyte antigen (HLA) class I molecules on the cell surface is necessary. There is increasing evidence that surface HLA class antigen expression is altered in a variety of human tumours by either loss or down-regulation of these molecules, which may be a strategy for evasion of immunosurveillance by malignant cells. This study has examined the expression of HLA class molecules in hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 34 publications
(38 reference statements)
1
28
0
1
Order By: Relevance
“…Immunohistochemical staining of HNSCC lesions has yielded conflicting data on TAP expression. Vora et al (17) reported that TAP1 and TAP2 were downregulated in only 2 (9%) and 0 (0%) of 34 primary HNSCC lesions tested, respectively. Feenstra et al (28) reported that TAP1 and TAP2 were downregulated in 28 Table III.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical staining of HNSCC lesions has yielded conflicting data on TAP expression. Vora et al (17) reported that TAP1 and TAP2 were downregulated in only 2 (9%) and 0 (0%) of 34 primary HNSCC lesions tested, respectively. Feenstra et al (28) reported that TAP1 and TAP2 were downregulated in 28 Table III.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining of frozen and/or formalin-fixed, paraffin-embedded HNSCC primary lesions has detected HLA class I antigen loss and downregulation with a frequency ranging from 6 to 81% (14)(15)(16)(17)(18)(19)(20)(21) information is available on the role of TAP1, TAP2 and tapasin defects in the generation of the abnormal HLA class I antigen phenotypes identified in HNSCC lesions. The lack of this information has a negative impact on the design of strategies to correct HLA class I antigen defects in HNSCC lesions.…”
Section: Introductionmentioning
confidence: 99%
“…HLA class I alleles differ in their requirements for antigen processing components; for example, tumors frequently exhibit alterations in the levels of TAP1-2, LMP2, LMP7, or tapasin expression [22][23][24]. Some alleles, such as HLA-A2, maintain their expression despite low levels of TAP1-2 or tapasin [25,26], whereas others, such as HLA-B44, have strict requirements for certain antigen processing components [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Although immunohistochemical analyses of HLA class I expression in several malignancies have previously been performed, there was a discrepancy in the frequencies of downregulated HLA class I molecules (Mattijssen et al, 1991;Möller et al, 1991;Passlick et al, 1996;Vora et al, 1997;Ramnath et al, 2006;Kikuchi et al, 2007;Mehta et al, 2008;Speetjens et al, 2008). This discrepancy might be due to a difficulty in evaluating immunostaining by anti-MHC class I monoclonal antibodies (mAbs), such as W6/32, HC-10, or HC-A2, as these anti-MHC class I mAbs were not appropriate for the immunostaining of formalin-fixed, paraffin-embedded tissue.…”
mentioning
confidence: 99%